Kaposi S sarcoma in Aids cases: study in 20 years of necropsy in university hospital - Corriça, Talita M.C. (2009)
Introduction: epidemic Kaposi’s sarcoma (KS) is the most frequent malignant neoplasia associated with acquired immunodeficiency syndrome (aids). In the 18 months that preceded the spring of 1981 an aggressive form of KS was identified in 21 homosexual and bisexual young men in the city of New York and in California. Objective: verify the occurrence of KS in aids during the years of 1985 through 2005 in a group of patients submitted to necropsy at the Serviço de Anatomia Patológica (SAP) at the Hospital Universitário Antonio Pedro (HUAP). Methods: a retrospective study of KS in aids patients was performed with analysis of post mortem gross reports and review of histological sections as well their clinical reports to confirm the diagnosis, the extent of the involvement of various organs and to establish clinical-pathological correlation of the data. Results: thirty-one cases of KS were identified in a total of 340 necropsies of aids patients, with prevalence in male gender (29:02) and white race (23:08). Skin was the most frequent organ involved and homosexual/bisexual patients identified as the most affected risk groups. Kaposi sarcoma could be attributed as cause of death in six cases although the most frequent cause of death was pulmonary complications. Conclusion: our study hilighted the importance of the analysis of necropsy data in the evaluation of KS in aids patients for the identification of epidemiological data of a selected population in a determined area, characterization of the form of the neoplastic dissemination and also the identification of morbidity and mortality factors.